Children using gestures and its integration with speech for communication: a comparative study between two age groups - Ibrahim, Sharjah (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English and Humanities, 2013.